Benzene--attempts to establish a lower exposure standard in the United States. A review. - Zenz, Carl (Scandinavian Journal of Work, Environment & Health, 1978)
Production usage and potential occupational exposure to benzene are described in this review, as are selected, relevant reports presenting evidence evidence implicating benzene as a causative factor in leukemia, particularly acute myelogenous leukemia, pancytopenia (including aplastic anemia) and chromosomal aberrations. A chronologic account of events in the 1970s in the United States, largely based on epidemiologic evdince collected and prepared by the National Institute for Occupational Safety and Health, caused the regulatory agency, the Department of Labor, through its Occupational Safety and Health Administration to declare benzene a human leukemogen and carcinogen and to publish an emergency temporary standard of 1 ppm in May, 1977, but this standard has not been legalized.
Keywords: anemia; aplastic anemia; benzene; chromosomal aberration; exposure; exposure standard; leukemia; occupational use; review; United States; United States regulations and standards; worker exposure